2018
DOI: 10.31234/osf.io/b3zju
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wanting without enjoying: The social value of sharing experiences

Abstract: Social connection can be a rich source of happiness. Humans routinely go out of their way to seek out social connection and avoid social isolation. What are the proximal forces that motivate people to share experiences with others? Here we used a novel experience-sharing and decision-making paradigm to understand the value of shared experiences. In seven experiments across Studies 1 and 2, participants demonstrated a strong motivation to engage in shared experiences. At the same time, participants did not repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…. $15.00 https://doi.org/10.1145/3383668.3419886 relationship quality, and feelings of closeness [3,9,10,15,21]. Most of our study participants agreed with these conclusions, reporting several barriers to collocated shared recreation with loved ones, while also expressing interest in technologies which may bridge these barriers.…”
Section: Introductionsupporting
confidence: 61%
“…. $15.00 https://doi.org/10.1145/3383668.3419886 relationship quality, and feelings of closeness [3,9,10,15,21]. Most of our study participants agreed with these conclusions, reporting several barriers to collocated shared recreation with loved ones, while also expressing interest in technologies which may bridge these barriers.…”
Section: Introductionsupporting
confidence: 61%
“…Why do individuals feel more connected after a shared experience? It has long been speculated that individuals form tighter social bonds after sharing a meal, watching a movie, or attending a concert or sporting event together and that they value and prefer shared experiences over solo experiences 1 . People may seek shared experiences because they provide opportunities for comparing their views of reality with others' 62 through which individuals can satisfy epistemic motives such as wanting to establish socially approved beliefs and worldviews 63 or relational motives such as the need for a sense of belonging 64 .…”
Section: Discussionmentioning
confidence: 99%
“…People value shared experiences 1 . Experiences in large groups such as religious ceremonies, music concerts, and sporting events often involve synchronization in movements, vocalizations, feelings, and thoughts with others, which has been thought to strengthen group cohesion [2][3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Jolly et al 14 suggested that such behavioral changes represent enhanced communicative or motivational behavior rather than an elevated subjective experience in co-presence situations. In a series of eight experiments, they failed to find an effect of shared attention on participants' emotional experience while they watched emotional video clips, although participants seemed to value shared experiences and were motivated to engage in them.…”
mentioning
confidence: 99%